An analysis of the risks of COVID-19 exposure to hospital employees at a private hospital in Yogyakarta, Indonesia - Khairunnisa, Qanita; Rosa, Elsye Maria; Pribadi, Firman; Ulfa, Maria (International Journal of Research in Medical Sciences, 2021)
Background: The healthcare workers provide the services to reduce morbidity and mortality rates. However, they are also exposed directly to the patients. WHO reports that 88% of health workers were infected with COVID-19 while working in hospitals, and 17% got exposure from communities. This study analyzes the overview of risk exposure to COVID-19 and risk factors of COVID-19 exposure to hospital employees at a private hospital in Yogyakarta during the COVID-19 pandemic. Methods: This study employs a quantitative approach with a cross-sectional design study. The data collecting is using an online questionnaire to assess the risk of COVID-19 exposure toward healthcare workers. Results: From 101 employees who participated to be the respondent, 13 employees had been diagnosed with COVID-19 during work in the COVID-19 pandemic. There was a significant difference between IPC compliance with the incidence of COVID-19 (p=0.046). Meanwhile, there were no significant differences between comorbidity (p=0.205) and duration of work (p=0.125) with the incidence number of COVID-19. Based on the ANOVA analysis, there was no significant difference between; IPC compliance, comorbidity, and duration of work with the incidence number of COVID-19 (p=0.092). Conclusion: The risk of healthcare workers exposed to COVID-19 could be through various factors within and outside the hospital. Compliance with IPC, comorbidities, and duration of work only affect as much as 6.4% of the incidence of COVID-19 among hospital employees.